2003
DOI: 10.1002/ffj.1183
|View full text |Cite
|
Sign up to set email alerts
|

Composition and antibacterial activity of the essential oil of Anisochilus carnosus (Linn. fil.) Benth., a Tamil plant acclimatized in Sicily

Abstract: The essential oil from aerial parts of Anisochilus carnosus (Linn. fil.) Benth. (Lamiaceae) was obtained by hydrodistillation. The oil content was 0.13% (v/w), on a fresh weight basis. The oil composition was analysed by GC and GC-MS and 28 compounds were identified, accounting for 94.3% of the oil. Carvacrol (27.9%), camphor (14.1%) and α-cis-bergamotene (10.2%) were the most abundant components. The oil is active against Gram-positive and Gram-negative bacteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…studied this substance constitutes from a few to several dozen percent, depending on the maturity of the flower heads (Table 2). Alpha-cis-bergamotene is the major component of oils that are characterised by antioxidant and antibacterial activity (Liu et al, 2012a,b;Senatore et al, 2003). Given the similarity of the chemical composition of the oils characteristic for both the arnica cultivars, it can be suggested that the analysed group of secondary metabolites should exhibit common biological properties, which is confirmed by the fact that A. montana and A. chamissonis flowers have been regarded as pharmaceutical raw material by the European Commission ().…”
Section: Tablementioning
confidence: 99%
“…studied this substance constitutes from a few to several dozen percent, depending on the maturity of the flower heads (Table 2). Alpha-cis-bergamotene is the major component of oils that are characterised by antioxidant and antibacterial activity (Liu et al, 2012a,b;Senatore et al, 2003). Given the similarity of the chemical composition of the oils characteristic for both the arnica cultivars, it can be suggested that the analysed group of secondary metabolites should exhibit common biological properties, which is confirmed by the fact that A. montana and A. chamissonis flowers have been regarded as pharmaceutical raw material by the European Commission ().…”
Section: Tablementioning
confidence: 99%
“…Its popular herbal preparation together with Ocimum basilicum, Mentha piperita and Alpinia galanga is used against the symptoms of influenza, dermatitis and the slight illness that derives from the bites of bugs (Subramanian and Nair, 1972). Essential oils have been extracted by hydrodistillation from the leaves and have been reported to be antimicrobial in nature (Senatore et al, 2003). The plant has been reported to have anti-inflammatory activity (Grover et al, 2001), antiulcer activity (Mohammed et al, 2008), antifungal property (Kulandhaivel et al, 2011) and anticancer property (Muthuraman et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Distribution in India is mainly seen in Karnataka, Maharashtra, Rajasthan, and Tamil Nadu and practiced traditionally in tribal communities for the treatment of ulcer, stomach ache, cough, and eczema. This plant's phytochemical study has revealed it to be rich in active compounds such as saponins, tannins, flavonoids (apigenin and luteolin), phytosterols, triterpenoids, and essential oil components (carvacrol, β-selinene, camphor, α-cis-bergamotene, and caryophyllene) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%